Assessment of immigrant detention centers and detainees health status in Libya - Adel El Taguri; Aisha Nasef (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2021)
Migrants are extremely vulnerable to various risks including the lack of physical and mental health care. The weakness of the health system in Libya is further undermined by the fragile, insecure, limited access, threats to health care workers and the increased social and economic challenges. This study studied the general environment of Detention Centers (DCs) of migrants in Libya and their health. Information were collected by during visits to DCs using to assess the structure, organization, financing, processes occurring in the center upon arrival of detainees, accommodation, water, sanitation and hygiene, food and nutrition, health-care services, and health status of detainees including their general health, chronic conditions, acute challenges as infections including TB, STD/HIV, hepatitis and malaria, and violence. Mental health was assessed using standard tools. Special questions were constructed for pregnant females and under five children. Sixteen DCs were visited. Thirteen of them had children in their premises, while ten detained women. Of the 427 interviewed, more than half were younger than 25 years of age. Overall environment and amenities were inadequate or poor. In more than half of DCs, deliveries did occur inside the DC itself. According to DCs managers, most common causes of death were TB, malnutrition and depression. The prevalence of acute and chronic illnesses including mental conditions were determined. Specific actions are proposed to each in particularly establishing/reviving a dedicated health center to meet the individual and public health needs of migrants.